Perilaku Siswa Dalam Penggunaan Sosial Media Di SMP Eka Sakti Semarang - Dahlia, Berlian Fitri; Indarwati, YM; Handayani, Dwi Asih (Emphaty Cons - Journal of Guidance and Counseling; Vol 3 No 1 (2021): Februari 2021DO - 10.31331/emp.v3i1.2021, 2022)
s